2022
DOI: 10.3389/fonc.2022.920843
|View full text |Cite
|
Sign up to set email alerts
|

Meaning and Significance of “Alkalization Therapy for Cancer”

Abstract: Objectives of the StudyOur research aims to answer the following questions. Can cancer progression be stopped by changing the body condition of person with cancer? Can cancer be cured?If cancer progression can be stopped, what is the underlying mechanism?Theoretical Rationale for Alkalization TherapyAlmost 70 years ago, Goldblatt H. & Cameron G. reported on the idea of alkalization therapy. Before that, Otto Warburg had been studying the metabolism of cancer and had discovered the essential nature of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…More research is needed on the mechanisms of the effectiveness of sodium bicarbonate and other buffer solutions in cancer patients. Alkalization (buffering) therapy does not conflict with standard treatment methods but can be used in combination to increase effectiveness ( 154 ).…”
Section: Tumor Acidity As a Target Of Treatmentmentioning
confidence: 99%
“…More research is needed on the mechanisms of the effectiveness of sodium bicarbonate and other buffer solutions in cancer patients. Alkalization (buffering) therapy does not conflict with standard treatment methods but can be used in combination to increase effectiveness ( 154 ).…”
Section: Tumor Acidity As a Target Of Treatmentmentioning
confidence: 99%
“…In a comparison of chemotherapy plus alkalization therapy versus chemotherapy alone in the treatment of advanced pancreatic cancer, the median OS was 15.4 (combination treatment group) vs. 10.8 months (chemotherapy alone group) ( p < 0.005) ( 9 ). Moreover, we previously found that patients with renal cancer, malignant lymphoma, gastric cancer, and breast cancer who were treated with alkalization therapy had favorable outcomes ( 10 ). As it remained unclear whether the combination of alkalization therapy with standard treatments would be as effective for HCC as for the cancers described above, we conducted a retrospective study of the effects of alkalization therapy on patients with HCC.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our group has encountered patients with renal cancer, malignant lymphoma, gastric cancer, and breast cancer in whom alkalization therapy increased their urine pH, which may have been associated with their favorable outcomes. However, these are only case reports and require further investigation ( 56 ).…”
Section: Clinical Reports Of Alkalization Therapy For Cancermentioning
confidence: 99%